Plutarch and the historical tradition - Stadter, Philip A. (Routledge, 1992)
These essays, by experts in the field from five countries, examine Plutarch's interpretative and artistic reshaping of his historical sources in representative lives. Diverse essays treat literary elements such as the parallelism which renders a pair of lives a unit or the themes which unify the lives. Others consider the selecting, combining, simplifying, and enlarging employed in composition. The construction of a Plutarchian life, the essays demonstrate, required careful selection and creative reworking of the historical material available.